American gulag : inside U.S. immigration prisons - Dow, Mark (University of California Press, 2004)
Before September 11, 2001, few Americans had heard of immigration detention, but in fact a secret and repressive prison system run by the U.S. Immigration and Naturalization Service has existed in this country for more than two decades. In American Gulag, prisoners, jailers, and whistle-blowing federal officials come forward to describe the frightening reality inside these INS facilities.